A pobreza urbana e a pobreza de direitos no Rio de Janeiro de Vargas | Urban poverty and the poverty of rights in the Rio de Janeiro of the Vargas era - Barone, Ana Cláudia (Revista Brasileira de Estudos Urbanos e Regionais, 2019)
Resenha do livro de Brodwyn Fischer, A Poverty of Rights, Citizenship and Inequality in Twentyeth-Century Rio de Janeiro, Stanford: Stanford University Press, 2008.